The Gq signalling pathway inhibits brown and beige adipose tissue - Katarina Klepac (Nature Portfolio, 2016)
Brown and beige adipose tissues contribute to organismal energy expenditure by generating heat. Here, Klepac et al. survey G protein-coupled receptors in brown fat and show that Gq-coupled receptors inhibit expression of thermogenic proteins in mice and in human adipocytes.